Comparison between jumping vs. cycling tests of short-term power in elite male handball players: the effect of age - Nikolaidis, P. T.; Torres-Luque, G.; Chtourou, H.; Clemente-Suarez, V. J.; Ramirez-Velez, R.; Heller, J. (Movement & Sport Sciences - Science & Motricité, 2016)
Purpose: The aim of the present study was to examine the effect of age on the relationship between jumping and cycling tests of short-term power in team handball (TH) players. Methods: A cross-sectional study was conducted, in which adolescent and adult TH players (n = 96, age 19.6±6.9 yrs, body mass 75.8±14.1 kg, height 1.78±0.10, mean±standard deviation) performed four jumping tests (i.e., squat jump, countermovement jump, Abalakov jump and a 30-s Bosco test), and two tests on cycle ergometer (i.e. force-velocity (F-v) test and Wingate anaerobic test (WAnT)). Heart rate (HR) was monitored during Bosco test and WAnT. Participants were classified into four age groups (12.1-15.0 yrs, U15; 15.1-18.0 yrs, U18; 18.1-25.0 yrs, U25; and 25.1-35.0 yrs, O25). Results: Differences of moderate to large magnitude among groups were observed with regards to all variables of the F-v test, WAnT and jumping tests, in which the older groups had higher scores in all variables than their younger counterparts (p < 0.05). Correlation between mean power in WAnT (8.0±1.0 W.kg-1) and Bosco test (29.3±7.1 W.kg-1) was r = 0.70 (p < 0.001) in the total sample (ranging from r = 0.43, p = 0.075 in O25 to r = 0.72 in U15, p < 0.001). Correlation between HR in WAnT (179±12 bpm) and Bosco test (162±14 bpm) was r = 0.75 (p < 0.001) in the total sample (ranging from r = 0.65, p < 0.001 in U18 to r = 0.81 in O25, p < 0.001). Conclusions: These findings might help TH coaches and fitness trainers to monitor short-term power of their athletes and to use properly cycling and jumping tests.